2003
DOI: 10.1001/archinte.163.14.1718
|View full text |Cite
|
Sign up to set email alerts
|

Azithromycin Monotherapy for Patients Hospitalized With Community-Acquired Pneumonia

Abstract: Azithromycin monotherapy is equally as efficacious as other ATS-recommended regimens for treating hospitalized patients with mild-to-moderate community-acquired pneumonia.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
19
0

Year Published

2005
2005
2016
2016

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(19 citation statements)
references
References 38 publications
0
19
0
Order By: Relevance
“…43 Numerous comparative studies have examined the mortality rate among patients hospitalized with CAP. [17][18][19][20][21][22]27,36,39,[44][45][46][47][48][49][50][51][52][53][54][55][56][57][58] Most were retrospective studies that compared different CAP management strategies. These studies demonstrated that the in-hospital mortality rate ranges from approximately 0% to 18% and the 30-day mortality rate ranges from 1% to 23%.…”
Section: Mortalitymentioning
confidence: 99%
See 2 more Smart Citations
“…43 Numerous comparative studies have examined the mortality rate among patients hospitalized with CAP. [17][18][19][20][21][22]27,36,39,[44][45][46][47][48][49][50][51][52][53][54][55][56][57][58] Most were retrospective studies that compared different CAP management strategies. These studies demonstrated that the in-hospital mortality rate ranges from approximately 0% to 18% and the 30-day mortality rate ranges from 1% to 23%.…”
Section: Mortalitymentioning
confidence: 99%
“…Reported 30-day readmission rates for CAP are Ͻ 1% to 20%. 21,22,27,45,46,50,51,65 In a study conducted in Edmonton, Alberta, from November 2000 to March 2006, 72% of patients with CAP were rehospitalized at least once. 26 Jencks et al 65 recently observed that among Medicare patients, the rehospitalization rate for those discharged with pneumonia (20%) was only slightly less than that for patients discharged with heart failure (27%) or COPD (23%).…”
Section: Mortalitymentioning
confidence: 99%
See 1 more Smart Citation
“…While the impact of empirical CAP antibiotic selection on outcomes has been evaluated in various patient care settings, limited information exists for Veterans Affairs (VA) patients (14,28), and we are unaware of any published CAP study that specifically examines the impact of combination therapy versus monotherapy for VA patients with severe CAP. It is difficult to generalize the findings of other studies to VA patients because of the vast differences in study populations: VA patients are typically older, with multiple comorbidities.…”
mentioning
confidence: 99%
“…Pseudomonas aeruginosa is a ubiquitous gram-negative opportunistic pathogen and a prevalent organism implicated in nosocomial infections (12). This bacterium has also been shown to be highly problematic in immunocompromised individuals (1,8,26).…”
mentioning
confidence: 99%